Acceptability and Nutrient Content of Wet Noodles Fortified with Inorganic or Organic Iron and Provitamin A from Pumpkin (Cucurbita moschata) - Ninik Rustanti; Retno Murwani; Syaiful Anwar (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTBackground: Iron fortification of wet noodles is a choice among many others, to reduce iron deficiency anemia. Organic andinorganic iron interact with provitamin A. An experiment was conducted to fortify wet noodles with organic and inorganic iron and provitamin A from pumpkin, and to study its effect on acceptance and its iron and provitamin A content.Methods: Six groups were used in this experiment to test optimal level of iron fortification (100 ppm, 150 ppm, 200 ppm of FeSO4 or organic iron). As for pumpkin, 10%, 15% and 20% were used. To test iron and provitamin A content, 5 groups were employed: wet noodle alone, wet noodle + (FeSO4), + (organic Fe), + (FeSO4 & pumpkin), and + (organic Fe & pumpkin) respectively. Data were evaluated by one-way ANOVA and continued by Duncan’s test with 95% CI.Result: Noodle fortified with 200 ppm iron was acceptable in term color, taste and texture. Adding 15% pumpkin improved texture optimally compared to 10% and 20%. In term color and taste, 10%, 15% and 20% pumpkin addition gave similar acceptance. Fortification of iron and provitamin A from pumpkin didn’t affect the moisture, protein, fat, fiber, and carbohydrate content but increased iron, ash and betacarotene content. Highest content of iron and provitamin A were found in noodles + (FeSO4 + pumpkin) and noodles + (organic Fe + pumpkin).Conclusion: Iron and provitamin A fortified wet noodles can serve as a choice for eliminating iron deficiency anemia in Indonesia. Further studies to see the bioavailability and effectiveness of fortified wet noodles to reduce anemia are needed.Keywords: Fortification, organic iron, inorganic iron, provitamin A pumpkin, wet noodlesABSTRAKDaya terima dan kandungan gizi mie basah yang difortifikasi zat besi anorganik dan organik serta provitamin A labu kuning (Cucurbita moschata)Latar belakang: Fortifikasi mie basah merupakan salah satu pilihan untuk menanggulangi permasalahan anemia gizi besi. Besi organik dan anorganik dapat berinteraksi dengan provitamin A. Penelitian ini bertujuan untuk memfortifikasi mie basah dengan besi organik dan anorganik serta provitamin A labu kuning, dan untuk mengetahui pengaruhnya terhadap daya terima, kadar besi dan provitamin A pada mie basah.Metode: Enam perlakuan digunakan dalam penelitian untuk optimasi kadar besi fortifikan (100 ppm, 150 ppm, dan 200 ppm FeSO4 atau Fe organik). Labu kuning yang digunakan 10%, 15%, dan 20%. Untuk mengetahui kadar besi dan provitamin A digunakan 5 perlakuan: mie basah, mie basah + (FeSO4), + (Fe organik), + (FeSO4 & labu kuning), dan + (Fe organik & labu kuning). Data dianalisis dengan one-way ANOVA dan dilanjutkan dengan uji Duncan dengan 95% CI.Hasil: Mie yang difortifikasi dengan 200 ppm zat besi dapat diterima dari sisi warna, rasa dan tekstur. Penambahan labu kuning 15% memberikan tekstur yang lebih baik dibandingkan 10% dan 20%. Dari sisi warna dan rasa, penambahan labu kuning 10%, 15% dan 20% mempunyai daya terima yang sama. Fortifikasi besi dan provitamin A labu kuning tidak mempengaruhi kadar air, protein, lemak, serat dan karbohidrat tetapi meningkatkan kadar besi, abu dan betakaroten. Kadar besi dan provitamin A tertinggi terdapat pada mie + (FeSO4 +labu) dan mie + (Fe organik + labu).Simpulan: Mie basah yang difortifikasi besi dan provitamin Aberupa labu kuning dapat menjadi alternatif untuk mengatasianemia gizi besi di Indonesia. Diperlukan penelitian lanjutanuntuk mengetahui bioavailabilitas dan keefektifan mie yangdifortifkasi untuk mengurangi anemia.